Pierwszy etap sowietyzacji Polski. Uwagi na marginesie leksykonu „Obozy i więzienia sowieckie na ziemiach polskich (1944–1945)” - Wolsza, Tadeusz (1956– ) (Instytut Historii PAN, 2024)
This review article provides a thorough analysis of the origins, development, and signifi cance of the NKVD camps on the Polish territories in 1944 and 1945. It concludes that these camps marked the initial phase of the Sovietisation of Poland.
Reviewed book: Obozy i więzienia sowieckie na ziemiach polskich (1944–1945). Leksykon, wstęp, opracowanie i redakcja naukowa Dariusz Iwaneczko, Rzeszów–Warszawa 2022, ss. 248 + ilustracje, mapy.
p. 243-258
Summaries in English.
Keywords: deportations; NKVD; camps; Smersh; repressions; Sovietisation; prisons - Poland - 1900-1945; World War, 1939-1945 - prisoners and prisons, Soviet - Poland